USE OF INFORMATION SYSTEMS TO DETERMINE PRODUCTIVE, REPRODUCTIVE AND POPULATION PARAMETER IN BUFFALOES AT BUFFALO FARM CALLED LA SUIZA LOCATED AT THE MAGDALENA MEDIO IN COLOMBIA - M. G. Cortes; L. C. Z. Giraldo; O. F. O. Rivera (Journal of Animal and Plant Sciences, 2012)
This research was conducted in the Hacienda Bufalera la Suiza, located in the Middle of the Magdalena River, Colombia; from January 2006 to December 2007. The aim of this study was to determine productive, reproductive and population parameters in buffaloes (Bubalus bubalis). Survey was conducted in the field information with historical data of population, reproductive and productive, and results from TaurusWebs Software. Total population analyzed was 3350 animals, divided into five age groups (infants 0-9 m, Growth I 9-12m, Growth II 12-18m, ending 18-24m and adults). Data were analyzed using descriptive statistics for subsystems and for this purpose was generated productivity trees time series for evaluation and assessment of delivery. The parameters generated by subsystems include: population: an inventory of animals on the farm, annual rate of replacement subsystem reproduction: conception buffalo heifers age, age at first calving, calving interval conception, calving interval. In the production subsystem: days in milk production, average production buffalo / day, milk production per day, total milk production, lactation duration, dry period, lactation curve, growth curve. From the descriptive analysis was performed a DOFA matrix for each subsystem. It made possible to determine age buffalo heifers conception average of 32.5 months (975 days), age at first calving averaged 44 months (1320 days), calving interval of 406 days, 205 days weight to 42.1 kilograms. Average production of buffalo milk per day is 3.3 liters, length of lactations averaging 284 days, dry period average length of 128 days.
Keywords: Buffaloes; parameters; Colombia